Sprachwandelphänomene im Unterricht Deutsch als Fremdsprache - Moraldo, Sandro M. (Kritik. Rivista di letteratura e critica culturale, 2023)
In recent years, the focus in foreign language teaching has shifted from the formal (grammatical) correctness of written and oral competencies in favor of the social and interactional dimension of language and communication. As a result, the linguistic consolidation of DaF/DaZ, but also DaM didactics has increased in importance. According to Eva Neuland and Corinna Peschel «a language didactics without a linguistic foundation, is no longer imaginable today». In this sense, my contribution pleads for the teaching of «realistic German» especially in the DaF/DaZ teaching context. For this purpose, it is important that not only the learners, but above all the teachers are provided with basic knowledge about aspects of spoken language and interactional linguistics and their didactic implementation. This will be exemplified by language change phenomena.